Effects of Smart City Construction on the Quality of Public Occupational Health: Empirical Evidence From Guangdong Province, China - Cheng, Hao; Wang, Fan-Fan; Dong, Da-Wei; Liang, Ji-Chao; Zhao, Chun-Fen; Yan, Bei (Frontiers in Public Health, 2021)
This paper takes Guangdong Province of China as the research object, first constructs the theoretical model of the impact of smart city construction on the quality of occupational health and puts forward the research hypothesis, and then uses the difference-in-difference model to evaluate the impact of smart city construction on the quality of public occupational health and inter-city differences. The results show that smart city construction significantly improves the quality of public occupational health, and this result is still valid after a serious of robustness tests. This policy effect is stronger in city which belongs to the region of the Pearl River Delta or the sub-provincial level city. This paper holds that central government should improve the pilot evaluation system and performance appraisal mechanism of smart city from the perspective of top-level design in the process of promoting smart city construction, which aims to correctly guide local governments to promote the construction of smart cities. In order to give full play to the improvement effect of smart city construction on the quality of public occupational health, local government should implement smart city strategy in a purposeful and planned way according to the actual situation of the development of the jurisdiction.